2022
DOI: 10.3126/qjmss.v4i1.45868
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Biases on Investment Decision Making: A Case of Pokhara Valley, Nepal

Abstract: Background: Behavioral finance deals with the study of psychological influences on investors and financial markets. Investors commonly perform investment analysis through fundamental and technical analysis. The behavior of the investment market originates from the principles of psychological decision-making that explains the reasons behind buying and selling stocks.   Objectives: This paper aims to examine the effect of cognitive biases on investment decisions in Pokhara Valley, Nepal. The effect of five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
7
1
1
Order By: Relevance
“…Anchoring Bias had the third highest impact on investment decisions. This contradicts the research by Dhungana et al (2022), which found that the effect of anchoring bias on investment decisions was statistically insignificant. However, the study by Dangol and Manandhar (2020) concluded that anchoring and adjustment factors significantly impacted the irrationality of investment decisions of Nepalese investors.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Anchoring Bias had the third highest impact on investment decisions. This contradicts the research by Dhungana et al (2022), which found that the effect of anchoring bias on investment decisions was statistically insignificant. However, the study by Dangol and Manandhar (2020) concluded that anchoring and adjustment factors significantly impacted the irrationality of investment decisions of Nepalese investors.…”
Section: Discussioncontrasting
confidence: 87%
“…The research by Dhungana et al (2022) &Gyanwali and Neupane (2021) also found that herding bias had a statistically significant effect on the investment decision of Nepalese investors. Anchoring Bias had the third highest impact on investment decisions.…”
Section: Discussionmentioning
confidence: 89%
“…However, a considerable portion of these studies primarily focuses on the equity market. Therefore, there is a crucial and essential need to explore the influence of behavioral biases on derivative market investors in the Indian subcontinent [51][52][53][54][55][56][57][58].…”
Section: Rathi and Geetha [46] Claim Big Five Personalitymentioning
confidence: 99%
“…Penelitian lain menunjukkan bahwa overconfidence bias memiliki pengaruh positif terhadap keputusan investasi cryptocurrency (Setiawan, Y. C., Atahau, A. D. R., & Robiyanto, R., 2018). Namun, penelitian lain menunjukkan bahwa overconfidence bias dapat menyebabkan kerugian pada investasi (Sihotang, A. E., & Pertiwi, T. K., 2021;Dhungana, B. R., Bhandari, S., Ojha, D., & Sharma, L. K., 2022). Oleh karena itu, terdapat perbedaan hasil penelitian mengenai pengaruh overconfidence bias terhadap keputusan investasi cryptocurrency di Purwakarta.…”
Section: Hasil Danunclassified